2019
DOI: 10.1073/pnas.1900052116
|View full text |Cite
|
Sign up to set email alerts
|

A role for S-nitrosylation of the SUMO-conjugating enzyme SCE1 in plant immunity

Abstract: SUMOylation, the covalent attachment of the small ubiquitin-like modifier (SUMO) to target proteins, is emerging as a key modulator of eukaryotic immune function. In plants, a SUMO1/2-dependent process has been proposed to control the deployment of host defense responses. The molecular mechanism underpinning this activity remains to be determined, however. Here we show that increasing nitric oxide levels following pathogen recognition promote S-nitrosylation of the Arabidopsis SUMO E2 enzyme, SCE1, at Cys139. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Nitric oxide has long been known as a regulator of pathogen defence responses in plants (Durner et al, 1998;Delledonne et al, 1998;Wang et al, 2009;Yun et al, 2011;Trapet et al, 2015;Skelly et al, 2019). Recently, Chandra et al, (2017) examined the involvement of the NO signal in CNP-triggered innate immunity in tea (Camellia sinensis).…”
Section: No Is Involved In Chitosan Nanoparticle-triggered Innate Imentioning
confidence: 99%
“…Nitric oxide has long been known as a regulator of pathogen defence responses in plants (Durner et al, 1998;Delledonne et al, 1998;Wang et al, 2009;Yun et al, 2011;Trapet et al, 2015;Skelly et al, 2019). Recently, Chandra et al, (2017) examined the involvement of the NO signal in CNP-triggered innate immunity in tea (Camellia sinensis).…”
Section: No Is Involved In Chitosan Nanoparticle-triggered Innate Imentioning
confidence: 99%
“…While less studies have been reported, the crosstalk between PTMs other than ubiquitination might also play important roles in the regulation of plant immunity. For example, the Arabidopsis SUMO E2 enzyme SCE1 is S -nitrosylated at Cys139 as a result of increased nitric oxide levels upon pathogen infection ( Skelly et al., 2019 ). Disabling the S -nitrosylation by mutation of Cys139 resulted in increased levels of SUMO1/2 conjugates, compromised immune responses, and elevated pathogen susceptibility.…”
Section: Crosstalk Between Non-ubiquitination Ptmsmentioning
confidence: 99%
“…Disabling the S -nitrosylation by mutation of Cys139 resulted in increased levels of SUMO1/2 conjugates, compromised immune responses, and elevated pathogen susceptibility. Thus, S -nitrosylation inhibits the SUMO-conjugating activity of SCE1, leading to relief of SUMO1/2-mediated suppression to drive immune activation ( Skelly et al., 2019 ). Interestingly, the SUMO-conjugating activity of UBC9, the human homolog of SCE1, is also inhibited following S -nitrosylation at Cys139, suggesting that this PTM crosstalk is conserved across phylogenetic kingdoms.…”
Section: Crosstalk Between Non-ubiquitination Ptmsmentioning
confidence: 99%
“…Protein S-nitrosylation has emerged as an important regulatory process in plants and hundreds of proteins have been identified as putative S-nitrosylated targets both in vitro and in vivo [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ]. However, •NO itself cannot directly react with cysteine thiols, but can readily condense with oxygen leading to the formation of nitrogen dioxide (•NO 2 ).…”
Section: Introductionmentioning
confidence: 99%